Dependable Flow and Flood Control Performance of Logung Dam, Central Java Province, Indonesia - Faza Ramadhani (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
The change of land use in Mt. Muria area Central Java has been resulting in the significant sheet erosion of upstream watershed around Mt. Muria, followed by considerably high sedimentation on rivers downstream that lead to the reduction of cross sections of the rivers including Logung River. Such situation has been contributing the condition that downstream of Logung River is very potential to experience over flow and inundation to its surrounding area. An idea of constructing the Logung Dam was introduced in 1986 that aimed at reducing the aforementioned inundation. Besides, the development of Logung Dam was also aimed at fulfilling both irrigation and non-irrigation water demand. This paper presents the results of the analysis of the water availability and flood control performance of the Logung Dam. The dependable flow was analyzed by applying the National Rural Electric Cooperative Association (NRECA) method in order to determine the low flow characteristics, whereas the identification of the high flow characteristics was carried out by using the Synthetic Unit Hydrograph (SUH) methods, i.e., the GAMA I and Nakayasu modeling approach. At a certain reservoir characteristic and a defined geometry of spillway, several reservoir routing simulations were carried out on both dependable flows and high flows. Results of the reservoir routing showed the promising water availability of the Logung Dam to fulfill water demand for both irrigation and non-irrigation, whereas the reservoir routing could reduce the probable maximum flood from QPMF from 1,031 m3/s to approximately 950 m3/s or damping efficiency at 7.86%. Further analysis suggests necessary operation and maintenance of Logung Dam to sustain its function and to mitigate possible problems related to reservoir sedimentation.